2004
DOI: 10.3310/hta8060
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and efficiency of guideline dissemination and implementation strategies

Abstract: Non-UK purchasers will have to pay a small fee for post and packing. For European countries the cost is £2 per monograph and for the rest of the world £3 per monograph.You can order HTA monographs from our Despatch Agents:-fax (with credit card or official purchase order) -post (with credit card or official purchase order or cheque) -phone during office hours (credit card only).Additionally the HTA website allows you either to pay securely by credit card or to print out your order and then post or fax it. NHS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
792
2
56

Year Published

2005
2005
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 2,328 publications
(897 citation statements)
references
References 27 publications
(21 reference statements)
23
792
2
56
Order By: Relevance
“…Others have proposed CRC risk assessment tools but with limited evaluation in practice (Freedman et al 2009;Kastrinos et al 2009). Printed educational materials have typically been shown to have small beneficial effects on professional practice (Farmer et al 2008;Grimshaw et al 2004). There were no significant improvements in awareness of the Periodic Health Examination Task Force recommendations for CRC screening and for routinely recommending FOBT screening for patients at population risk of CRC.…”
Section: Discussionmentioning
confidence: 99%
“…Others have proposed CRC risk assessment tools but with limited evaluation in practice (Freedman et al 2009;Kastrinos et al 2009). Printed educational materials have typically been shown to have small beneficial effects on professional practice (Farmer et al 2008;Grimshaw et al 2004). There were no significant improvements in awareness of the Periodic Health Examination Task Force recommendations for CRC screening and for routinely recommending FOBT screening for patients at population risk of CRC.…”
Section: Discussionmentioning
confidence: 99%
“…Risk ratios and 95% confidence intervals (CIs) were calculated for dichotomous outcomes, and the percentage mean difference in the change scores 30 with 95% CIs were calculated for continuous outcomes. Variation inflation factors could not be calculated from the available raw data, and these studies could not be adjusted for clustering.…”
Section: Data Synthesis and Analysismentioning
confidence: 99%
“…There is a paucity of evidence on the effectiveness of knowledge translation interventions among rehabilitation professionals (Menon et al, 2009). However, systematic reviews of interventions aimed at changing health professional behavior have shown a variety of interventions including the dissemination of educational materials to have modest effects (Grimshaw et al, 2004). Case studies sent by e-mail have been used as an effective means of continuing health professional education, resulting in significant improvements in knowledge, confidence and communication compared to controls (Kemper et al, 2002).…”
Section: Introductionmentioning
confidence: 99%